2010
DOI: 10.1007/s10804-010-9099-2
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction, Sense of Coherence and Job Precariousness in Italian Young Adults

Abstract: We investigated (in 95 Italians aged 19-29, of both genders, and who were all facing the transition to job):(1) the relationships between job precariousness, life satisfaction (LS), and the perception that the reality is comprehensible, manageable and meaningful (sense of coherence-SOC-Antonovsky 1987); (2) the potential buffering effect of SOC versus job precariousness on LS. The findings showed that (a) young adults with a higher level of education perceive less LS and higher manageability, and youths with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Since 2003, the SOC-29 and the SOC-13 has been used in a further 13 countries (Eriksson, 2014): Eritrea (Almedom et al, 2007), Croatia (Pavicic Bosnjak, Rumboldt, Stanojevic, & Dennis, 2012), Hungary (Biro et al, 2010), India (Suraj & Singh, 2011), Iran (Rohani et al, 2010), Italy (Ciairano, Rabaglietti, Roggero, & Callari, 2010), Korea (Han et al, 2007), Kosovo, the Democratic Republic of Congo (Pham et al, 2010), Spain (Virues-Ortéga, Martinez-Martin, Del Barrio, Lozano, & Grupo Espanol, 2007), Sudan (Abdelgadir, Shebeika, Eltom, Berne, & Wikblad, 2009), Taiwan (Tang & Li, 2008), and Turkey (Ö ztekin & Tezer, 2009). More recent research shows three additional countries: Austria (Mautner et al, 2014), Estonia (Höjdahl, Magnus, Mdala, Hagen, & Langeland, 2015), and Malaysia (Rostami, Lamit, Khoshnava, & Rostami, 2014).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…Since 2003, the SOC-29 and the SOC-13 has been used in a further 13 countries (Eriksson, 2014): Eritrea (Almedom et al, 2007), Croatia (Pavicic Bosnjak, Rumboldt, Stanojevic, & Dennis, 2012), Hungary (Biro et al, 2010), India (Suraj & Singh, 2011), Iran (Rohani et al, 2010), Italy (Ciairano, Rabaglietti, Roggero, & Callari, 2010), Korea (Han et al, 2007), Kosovo, the Democratic Republic of Congo (Pham et al, 2010), Spain (Virues-Ortéga, Martinez-Martin, Del Barrio, Lozano, & Grupo Espanol, 2007), Sudan (Abdelgadir, Shebeika, Eltom, Berne, & Wikblad, 2009), Taiwan (Tang & Li, 2008), and Turkey (Ö ztekin & Tezer, 2009). More recent research shows three additional countries: Austria (Mautner et al, 2014), Estonia (Höjdahl, Magnus, Mdala, Hagen, & Langeland, 2015), and Malaysia (Rostami, Lamit, Khoshnava, & Rostami, 2014).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…Since 2003, the SOC-29 and the SOC-13 has been used in a further 13 countries (Eriksson, 2014): Eritrea (Almedom et al, 2007), Croatia (Pavicic Bosnjak, Rumboldt, Stanojevic, & Dennis, 2012), Hungary (Biro et al, 2010), India (Suraj & Singh, 2011), Iran (Rohani et al, 2010), Italy (Ciairano, Rabaglietti, Roggero, & Callari, 2010), Korea (Han et al, 2007), Kosovo, the Democratic Republic of Congo (Pham et al, 2010), Spain (Virues-Ortéga, Martinez-Martin, Del Barrio, Lozano, & Grupo Espanol, 2007), Sudan (Abdelgadir, Shebeika, Eltom, Berne, & Wikblad, 2009), Taiwan (Tang & Li, 2008), and Turkey (Ö ztekin & Tezer, 2009). More recent research shows three additional countries: Austria (Mautner et al, 2014), Estonia (Höjdahl, Magnus, Mdala, Hagen, & Langeland, 2015), and Malaysia (Rostami, Lamit, Khoshnava, & Rostami, 2014).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…Research has found that a precarious job condition may affect the psychological adjustment of people similarly to that of unemployment (De Witte, 2005;Sverke & Hellgren, 2002) and that the impact of job uncertainty and insecurity has been observed on an individual's health, stress and on one's identity corrosions and anomie's promotions (De Witte, 1999;Sennet, 1998;Sutin & Costa, 2010;Uchitelle, 2006). Besides, job insecurity may have adverse psychological effects in terms of psychosomatic symptoms and anxiety, high rates of depression, and low levels of life satisfaction and self-esteem (e.g., Ciairano, Rabaglietti, Roggero, & Callari, 2010;McKee-Ryan, Song, Wanberg, & Kinicki, 2005;Paul & Moser, 2009). Thus, focusing on young adults' first entry into the labour market when studying the transition to adulthood is crucial if we consider this transition as a step-by-step process in which individuals take on responsibilities in various life domains and increasingly participate in "adult activities" (Corijn & Klijzing, 2001;Hogan & Astone, 1986).…”
Section: Working Status and Transition To Adulthoodmentioning
confidence: 99%